Anna Branach-Kallas and Piotr Sadkowski. Comparing Grief in French, British and Canadian Great War Fiction (1977-2014). Brill, 2018. - Erika Quinn (Studies in 20th & 21st Century Literature, 2019)
Review of Anna Branach-Kallas and Piotr Sadkowski. Comparing Grief in French, British and Canadian Great War Fiction (1977-2014). Brill, 2018. 251 pp.
Keywords: grief; French fiction; British fiction; Canadian fiction; Great War